PANDANGAN ORANG TUA DALAM PENGGUNAAN APLIKASI MEDIA SOSIAL DI ANAK REMAJA (STUDI KASUS: KOTA SURABAYA) - Riswandha Imawan, Moh; Rifqi Zamzami, Moh; Ghozali, Imam (Lafadz Jaya Publisher, 2023)
In this study, the aim is to find out how parents view the use of social media applications in adolescents in the city of Surabaya. The research method used is descriptive qualitative, which is done by collecting data through interviews and observation. The results of this research show that various views of parents of teenagers in the city of Surabaya range from positive, negative, and neutral. There are many positive and negative impacts on teenagers in using social media; there are positive impacts obtained from teenagers, namely: being able to strengthen friendships with friends, being able to add friends, easy to interact with friends, being easy to get along with, broadening knowledge, make social media as a discussion suggestion, a place to pour out your heart, a place to store personal data. Meanwhile, the negative impacts that occur on adolescents in using social media are: imitation behavior, offense, reduced relationship with the surrounding environment, forgetting time from study time and other activity times, and the most important negative impact is lack of attention to family. Teenagers in the city of Surabaya use social media not only to chat and watch videos but also to act as content creators. but there is an impact that parents complain about, like teenagers, they often create content such as content that is considered bad and can forget about their own obligations.